Phytochemical constituents of the flowers of Sarcococca coriacea of Nepalese origin - Rai, N. P.; Adhikari, B. B.; Paudel, Arjun; Masuda, K.; Mckelvey, R. D.; Manandhar, M. D. (Journal of Nepal Chemical Society, 2006)
From the flowers of Sarcococca coriacea, a triterpenoic acid, oleanolic acid, a pentahydric sugar alcohol, xylitol along with the mixture of steroidal glycosides, stigmasterol-3-O-β-D-glucopyranoside and β-sitosterol-3-O-β-D-glucopyranoside have been isolated by chromatographic technique. Their structures were established on the basis of IR, 1H-NMR, 13C-NMR, spectral data as well as melting point and Co-TLC comparison with the authentic samples. DOI: 10.3126/jncs.v21i0.214 Journal of Nepal Chemical Society Vol.21 2006 p.1-7